Risk of metabolic syndrome and early vascular markers for atherosclerosis in obese Indonesian adolescents. (2nd April 2020) - Murni, Indah K.; Sulistyoningrum, Dian C.; Susilowati, Rina; Julia, Madarina
ABSTRACT: Background : The prevalence of childhood obesity has increased in low- and middle-income countries, including Indonesia. It is important to identify risk factors for cardiovascular disease in obese adolescents in this region. Aim : To assess the risk of metabolic syndrome and early vascular markers for atherosclerosis in obese Indonesian adolescents Methods : A cross-sectional study was undertaken in obese high school students aged 15–<18 years in Yogyakarta, Indonesia. All eligible adolescents were interviewed about their medical history, were physically examined and had a fasting blood sample taken. Arterial stiffness was measured during systole and diastole blood pressure, endothelial dysfunction was estimated using flow-mediated dilation (FMD) and arterial wall thickness using carotid artery intima-media thickness (CIMT). Results : A total of 4268 students were screened, 298 (7%) of whom were classified as obese. Of those, 229 had blood samples taken, 173 had FMD performed and 156 had CIMT examination. Adolescents with a higher body mass index or BMI Z- score (>3.0) had a significantly poorer lipid profile, insulin level and homeostasis model assessment of insulin resistance (HOMA-IR) than those with a lower BMI Z- score. There were no significant differences for early vasculature markers for atherosclerosis between these two groups. Conclusion : The prevalence of risks of cardiovascular disease in obese adolescents was significant. The higher the BMI Z- score, the higher the risks of cardiovascular disease. Interventions to reduce obesity and its cardiovascular disease morbidities are urgently needed in low- and middle-income countries. Abbreviations : BMI; body mass index; CIMT, carotid artery intima-media thickness; CDC, Centers for Disease Control and Prevention; FMD flow-mediated dilation; HDL high-density lipoprotein cholesterol; HbA1c haemoglobin A1c; HOMA-IR, homeostasis model assessment of insulin resistance; IOTF, International Obesity Task Force; LDL, low-density lipoprotein cholesterol; WHO, World Health Organization